2022
DOI: 10.3390/brainsci12091185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Repetitive Transcranial Magnetic Stimulation on Gait and Postural Control Ability of Patients with Executive Dysfunction after Stroke

Abstract: Objective: To assess the effects of repetitive transcranial magnetic stimulation (rTMS) on the gait and postural control ability of patients with executive dysfunction (ED) after stroke. Methods: A total of 18 patients with ED after stroke were randomly assigned into two groups, including an experimental group and a sham group. Patients in both groups received routine rehabilitation therapy, and patients in the experimental group underwent rTMS on the left dorsolateral prefrontal cortex (DLPFC) for 2 weeks (5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…After further review of titles and abstracts, 88 studies were reserved. Finally, 61 studies 14–74 were included after a review of the full text. Figure 1 shows the literature screening process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After further review of titles and abstracts, 88 studies were reserved. Finally, 61 studies 14–74 were included after a review of the full text. Figure 1 shows the literature screening process.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 61 studies, a total of 28 studies 14,18–21,23–25,30–32,34,35,37,39–41,47,49,51,52,54,57,59,66,69,73,74 used a frequency of 10 Hz for HF-rTMS, 13 studies 15,22,26,29,33,38,44,45,61,65,67,68,71 used 5 Hz, and the others used 2–50 Hz. The resting motor threshold (MT) is the minimum intensity of TMS stimulation of a fully relaxed muscle that elicits an electromyograph response of at least 50 μV with a probability of 50%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Intermittent theta burst stimulation (iTBS), which is a special mode of repetitive transcranial magnetic stimulation, has been demonstrated to regulate the excitability of the cerebral cortex and induce plastic changes in the cortex ( Lowe et al, 2018 ). One study found that rTMS over the DLPFC could improve the postural control ability by in patients after stroke ( Yu et al, 2022 ). After the intervention of iTBS on the left DLPFC, the performance during working memory tasks in healthy participants was improved by increasing the theta connectivity between the frontal and parietal regions ( Hoy et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%